2014
DOI: 10.1111/age.12240
|View full text |Cite|
|
Sign up to set email alerts
|

The brown coat colour of Coppernecked goats is associated with a non‐synonymous variant at the TYRP1 locus on chromosome 8

Abstract: The recent development of a goat SNP genotyping microarray enables genome-wide association studies in this important livestock species. We investigated the genetic basis of the black and brown coat colour in Valais Blacknecked and Coppernecked goats. A genome-wide association analysis using goat SNP50 BeadChip genotypes of 22 cases and 23 controls allowed us to map the locus for the brown coat colour to goat chromosome 8. The TYRP1 gene is located within the associated chromosomal region, and TYRP1 variants ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 15 publications
0
29
1
1
Order By: Relevance
“…) and tyrosinase‐related protein 1 ( TRYP1 ) (Becker et al . ). Due to religious or cultural preferences, multiple coat colour patterns are present in Pakistani breeds, including solid white (phaeomelanic), white/brown (anterior), solid dark brown, solid light brown, white/black (eumelanic and tan light belly) and white with black spots (Table ).…”
Section: Introductionmentioning
confidence: 97%
“…) and tyrosinase‐related protein 1 ( TRYP1 ) (Becker et al . ). Due to religious or cultural preferences, multiple coat colour patterns are present in Pakistani breeds, including solid white (phaeomelanic), white/brown (anterior), solid dark brown, solid light brown, white/black (eumelanic and tan light belly) and white with black spots (Table ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, tyrosinase-related protein 1 (TYRP1) is a strong candidate gene for coat color variation in Soay sheep (Gratten et al, 2007). Recently, researchers have focused on associations between candidate genes and coat color in goat, such as the red and black coat color phenotypes that are associated with MC1R ) and the brown coat color associated with TYRP1 variants (Becker et al, 2015;Dietrich et al, 2015). However, no single locus has been found to explain all of the divergence in coat color phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…TYRP1 mutations produce brown phenotypes in dog, cattle, sheep, cat and Japanese quail (Berryere et al 2003; Gratten et al 2007;Lyons et al 2005;Nadeau et al 2007;Schmutz et al 2002). A previous study with Bionda dell'Adamello goats showed that the genotype frequency distribution of a non-synonymous SNP (G1112A) suggested a possible role for TYRP1 in brown eumelanic coat color, whereas another report showed that the brown coat color of Coppernecked goats is associated with a nonsynonymous variant (p.Gly496Asp) at the TYRP1 locus (Becker et al 2015;Nicoloso et al 2012). Similarly, we found that TYRP1 showed higher expression level in brown goat skin than in white goat skin and gray goat skin, whereas there were no differences in expression between the gray and white skin samples.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse fur colors in mammals are mainly determined by the relative quantities of eumelanin and pheomelanin and the distribution of these pigments in the body (Cieslak et al 2011;Ito and Wakamatsu 2008;Ito et al 2000). Many genes, such as Melanocortin 1 receptor (MC1R), Agouti signaling protein (ASIP), Microphthalmiaassociated transcription factor (MITF), KIT Proto-Oncogene Receptor Tyrosine Kinase (KIT), Premelanosome protein (PMEL), Transient receptor potential cation channel subfamily M member 1 (TRPM1), Tyrosinase (TYR), Tyrosinase-Related Protein 1 (TYRP1), and Dopachrome tautomerase (DCT) are involved in melanin production and are therefore likely to be involved in determining fur color (Bauer et al 2009;Becker et al 2015;Deng et al 2009;Gratten et al 2007;Kijas et al 1998;Marklund et al 1999;Mundy and Kelly 2006;Norris and Whan 2008;Paterson et al 2015;Philipp et al 2005;Slominski et al 2004;Steingrimsson et al 2006). However, the mechanisms by which these genes act to produce fur color is unclear.…”
Section: Introductionmentioning
confidence: 99%